(untitled) (Research, Society and Development, 2022)
The need for multicultural education is a reality, which can be referred as cultural competence or even cultural sensitivity, especially that directed at health professionals who care for indigenous people. The research aimed to understand the experiences of health professionals on the qualification of care directed to indigenous population, especially in the transition of care. Through a semi-structured questionnaire, interviews were conducted with professionals experienced in the transition of care for Xikrin indigenous people in a city in Southeast Pará (Brazil). The transcripts of the interviews were followed by content analysis. We observed that the difficulty in communication affects both the quality of the continuity of treatment and the adherence by the indigenous population. The breadth of the difficulty, both due to the cultural factor and the professional training, is possibly due to a gap in academic education.